Antibody Responses and Clinical Outcomes in Adults Hospitalized With Severe Coronavirus Disease 2019 (COVID-19): A Post hoc Analysis of LOTUS China Trial. (25th August 2020) - Ren, Lili; Fan, Guohui; Wu, Wenjuan; Guo, Li; Wang, Yeming; Li, Xia; Wang, Conghui; Gu, Xiaoying; Li, Caihong; Wang, Ying; Wang, Geng; Zhou, Fei; et al.
Abstract: Background: The characteristics of neutralizing antibodies (NAbs) and antibody against major antigen proteins related to clinical outcomes in severe coronavirus disease 2019 (COVID-19) patients were still less known. Methods: NAbs and antibodies targeting nucleocapsid (N), spike protein (S), and the receptor-binding domain (RBD) in longitudinal plasma samples from the LOTUS China trial were measured by microneutralization assay and enzyme-linked immunosorbent assay (ELISA). Viral load was determined by real-time reverse transcription polymerase chain reaction (RT-PCR). A total of 576 plasma and 576 throat swabs were collected from 191 COVID-19 patients. Antibody titers related to adverse outcome and clinical improvement were analyzed. Multivariable adjusted generalized linear mixed model for random effects were developed. Results: After day 28 post symptoms onset, the rate of antibody positivity reached 100% for RBD-immunoglobulin M (IgM), 97.8% for S-IgM, 100% for N-immunoglobulin G (IgG), 100% for RBD-IgG, 91.1% for N-IgM, and 91.1% for NAbs. The NAbs titers increased over time in both survivors and nonsurvivors and correlated to IgG antibodies against N, S, and RBD, whereas its presence showed no statistical correlation with death. N-IgG (slope −2.11, 95% confidence interval [CI] −3.04 to −1.18, P < .0001), S-IgG (slope −2.44, 95% CI −3.35 to −1.54, P < .0001), and RBD-IgG (slope −1.43, 95% CI −1.98 to −.88, P < .0001) were negatively correlated with viral load. S-IgG titers were lower in nonsurvivors than survivors ( P = .020) at week 4 after symptoms onset. Conclusions: IgM and IgG against N, S, and RBD and NAbs developed in most severe COVID-19 patients and do not correlate clearly with clinical outcomes. The levels of IgG antibodies against N, S, and RBD were related to viral clearance. Abstract : IgM, IgG against N, S and RBD and NAbs developed in most severe COVID-19 patients, and do not correlate clearly with clinical outcomes. The levels of IgG antibodies against N, S and RBD were related to viral clearance.